2020
DOI: 10.1111/csp2.179
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the presence of feral cat colonies and Toxoplasma gondii in relation to bird conservation areas on O'ahu, Hawai'i

Abstract: Free-ranging feral cats (Felis catus) are increasingly found in colonies loosely managed by people. These colonies increase cat densities and, hence, pose threats to wildlife via disease and predation, particularly in insular ecosystems where native species have smaller populations and reduced pathogen exposure compared to continental systems. Given such concerns, our objectives were to: (a) identify feral cat colonies on the island of O'ahu in the vicinity of important native bird sites;and (b) test for Toxop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Thus, 11 geese died of toxoplasmosis. The presence of cats in colonies near the native bird sites is thought to be a source of T. gondii oocysts for the birds (Lepczyk et al , 2020).…”
Section: Clinical Toxoplasmosis In Wild Birdsmentioning
confidence: 99%
“…Thus, 11 geese died of toxoplasmosis. The presence of cats in colonies near the native bird sites is thought to be a source of T. gondii oocysts for the birds (Lepczyk et al , 2020).…”
Section: Clinical Toxoplasmosis In Wild Birdsmentioning
confidence: 99%
“…In particular, the impact of predation on native species by cats is serious on islands where no predatory mammals were historically present (Bonnaud et al 2011;Medina et al 2011;Nogales et al 2013;Courchamp et al 2003), contributing to the extinction of at least 63 vertebrate taxa (Loss and Marra 2017). Other issues related to free-ranging cats include the transmission of infections, such as toxoplasmosis and toxocariasis (Deplazes et al 2011;Macpherson 2013;Gerhold and Jessup 2013;Lepczyk et al 2020;Wilson et al 2020) or hybridization with the wildcat (Felis silvestris) (Pierpaoli et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Four domestic cat shedding studies were identified in island countries or continents where native wild felid species are absent, specifically New Zealand, Australia, and St. Kitts. In addition, two recent studies from the island of O'ahu (Hawaii, USA), where wild felids are also absent, detected T. gondii DNA in faeces from domestic cats (7% and 10.7% of cats tested), but these studies did not examine faeces microscopically for the presence of oocysts (Davis et al., 2018; Lepczyk et al., 2020).…”
Section: Resultsmentioning
confidence: 99%